Bridging the divide: New evidence about firms and digitalisation - Reinhilde Veugelers; Désirée Rückert; Christoph Weiss (Bruegel, 2019)
Using new evidence on the digitalisation activities of firms in the European Union and the United States, we document a trend towards digital polarisation based on firms' use of the latest digital technologies and their plans for future investment in digitalisation. A substantial share of firms are not implementing any state-of-the-art digital technologies and do not have plans to invest in digitalisation. However, there is also a substantial share of firms that are already partially or even fully implementing state-of-the-art digital technologies in their businesses and that plan to further increase their digitalisation investments. Small Manufacturing firms and old small firms in services are significantly more likely to be and remain non-active in terms of digitalisation. Our results do not provide any evidence that EU firms are more likely than their US counterparts to be stuck on the wrong side of the digitalisation divide. Taking into account firm size and firm age, there are no significant differences between the EU and the US in terms of having more or fewer persistently non-digital firms. As persistently digitally-inactive firms are also less likely to be innovative, to add employees or to command higher mark-ups, it is important for policymaking to remove barriers that trap these firms in persistent digital inactivity. Lack of access to finance is a major barrier for EU firms compared to their US counterparts, particularly for the EU's persistently non-digital firms, and especially for older, smaller companies in services. Improving their access to finance might therefore go a long way towards addressing the corporate digitalisation divide in the EU.
Keywords: 330